2009
DOI: 10.1002/pros.20988
|View full text |Cite
|
Sign up to set email alerts
|

The increased expression of periostin during early stages of prostate cancer and advanced stages of cancer stroma

Abstract: POSTN, one of the 3DC-associated genes, may serve as a potential biomarker for predicting the pathological grade and prognosis of CaP. Prostate 69: 1398-1403, 2009. (c) 2009 Wiley-Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 21 publications
6
39
1
Order By: Relevance
“…Increased expression of POSTN has been observed in various tumor types, including breast [44,48,[56][57][58], NSCLC [27,49,[59][60][61][62], colorectal [19,29,63], stomach cancers [64][65][66][67][68], pancreatic [32,69], prostate [70][71][72][73][74][75], ovarian cancer [76][77][78][79], and glioblastomas [80][81][82] (Table 1).…”
Section: Periostin Expression In Different Types Of Tumorsmentioning
confidence: 99%
“…Increased expression of POSTN has been observed in various tumor types, including breast [44,48,[56][57][58], NSCLC [27,49,[59][60][61][62], colorectal [19,29,63], stomach cancers [64][65][66][67][68], pancreatic [32,69], prostate [70][71][72][73][74][75], ovarian cancer [76][77][78][79], and glioblastomas [80][81][82] (Table 1).…”
Section: Periostin Expression In Different Types Of Tumorsmentioning
confidence: 99%
“…In addition, high reactive stromal grading is associated with lower biochemical recurrence-free survival rates than low reactive stromal grading [Ayala et al, 2003;Yanagisawa et al, 2007]. Recently, we have reported that periostin expression in CAFs was increased in the early stages of PCa tissues (Gleason score 6-7) and was significantly correlated with the degree of malignancy [Tsunoda et al, 2009]. Upregulation of collagen I, tenascin-C (TN-C), and transforming growth factor b (TGFb) have been observed in PCa specimens [Tuxhorn et al, 2002a].…”
mentioning
confidence: 94%
“…The roles of periostin have also been reported in human bladder and prostate cancer tissues. Epithelial and stromal expression of periostin in normal prostate was detected in 74 and 13% of tissues examined, respectively (23). Periostin expression increased in the early stages of prostate cancer (Gleason score 6-7) but not in the advanced stages of prostate cancer.…”
Section: Discussionmentioning
confidence: 93%